Antecedents of Individuals' Interteam Coordination: Broad Functional Experiences as a Mixed Blessing - de Vries, Thomas A.; Walter, Frank; Van der Vegt, Gerben S.; Essens, Peter J. M. D. (Academy of Management Journal, 2014)
This manuscript investigates the role of individual team members' breadth of functional experience for their interteam coordination behavior. Integrating personal construct and social identity theories, we examine interpersonal cognitive complexity as a mediating variable and organizational identification as a moderator. We test our hypotheses across two independent field studies, comprising an international peace support training mission (Study 1) and a municipality administration (Study 2). Corroborating our predictions, interpersonal cognitive complexity appeared as a conditional mediating variable that can translate an individual's breadth of functional experience into interteam coordination. The strength and direction of this indirect relationship, however, depended on the individual's identification with the organization as a whole. Moreover, on the team level of analysis, we found members' overall interteam coordination to positively relate with team performance in Study 2. All in all, this paper advances new knowledge on the antecedents, mechanisms, contingency factors, and team-level consequences of members' boundary spanning.